(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This study investigated the inhibitory effect of methanol-water extract and different fractions on soil properties, herbage yield, and quality of the medicinal herb Senna. The results showed that the methanol-water extract and fractions had no significant anti-tyrosinase activity, but some fractions were active toward α-glucosidase. The hexane fraction and remaining crude extract demonstrated the highest inhibition on α-glucosidase compared to acarbose. ENC and BFM were compared with conventional farmyard manure (FYM) and chemical fertilizers (CF) in a pot experiment. Both ENC and EBC improved soil quality and fertility by increasing soil organic carbon, available nutrients, microbial biomass, and enzyme activity. ENC and BFM increased total herbage yields by 21 and 16.3% compared to FYM. The ethyl acetate fraction contained high phenolic and hydroxy anthraquinone derivatives, but no correlation was observed between the phenolic and sennoside contents of different fractions and their α-glucosidase inhibitory effect. The hexane fraction of C. angustifolia could be valuable for in vitro and in vivo antidiabetic studies and further phytochemical studies.